The physiology and psychophysics of the color-form relationship: a review - Moutoussis, Konstantinos (Frontiers in Psychology, 2015)
The relationship between colour and form has been a long standing issue in visual science. A picture of functional segregation and topographic clustering emerges from anatomical and electrophysiological studies in animals, as well as by brain imaging studies in human. However, one of the many roles of chromatic information is to support form perception, and in some cases it can do so in a way superior to achromatic (luminance) information. On the other hand, form seems a necessary prerequisite for the computation and assignment of colour across space, and there are several examples in which the colour of an object can be influenced by its form. Chromatic information can support form perception almost as equally well as luminance information can, both at an early, contour-detection stage, as well as in late, higher stages involving spatial integration and the perception of global shapes. Pure chromatic contrast can also support several visual illusions related to form-perception. Electrophysiological studies have revealed neurons in the visual brain able to signal contours determined by pure chromatic contrast, the spatial tuning of which is similar to that of neurons carrying luminance information. It seems that, especially at an early stage, form is processed by several, independent systems that interact with each other, each one having different tuning characteristics in colour space. At later processing stages, mechanisms able to combine information coming from different sources emerge. A clear interaction between colour and form is manifested by the fact that colour-form contingencies can be observed in various perceptual phenomena such as adaptation aftereffects and illusions. Such an interaction suggests a possible early binding between these two attributes, something that has been verified by both electrophysiological and fMRI studies.